Engaging Students With Game-Based Learning: A Case Study of English Motivation at The Fifth Grade Students of SD Islam Al-Azhar 51 Kota Bengkulu - Ahmad Choky Alamsya Hidaya; Fera Zasrianita; Andriadi Andriadi (Journal of Innovative and Creativity, 2025)
This study addresses the limited research on the use of Game-Based Learning (GBL) in supporting English motivation and engagement at the elementary school level. It aims to investigate how the implementation of GBL supports students’ learning motivation and the factors influencing their engagement. A mixed-method design was employed, combining qualitative and quantitative approaches involving 29 fifth-grade students at SD Islam Al Azhar 51 Kota Bengkulu. The findings indicate that the implementation of GBL supports students’ motivation in learning English, as reflected in their enthusiasm, attention, and active participation through interactive games, collaborative activities, and teacher guidance. In addition, students’ engagement in GBL-based learning is influenced by internal factors such as enjoyment, interest, self-confidence, and awareness of the importance of English, as well as external factors including the types of games used, their alignment with lesson content, teacher strategies, peer collaboration, and the overall classroom environment. These elements together contribute to a dynamic, student-centered environment that strengthens positive attitudes toward English learning.